"Intensity-Response" Effects of Electroacupuncture on Gastric Motility and Its Underlying Peripheral Neural Mechanism. (1st July 2013) - Su, Yang-Shuai; He, Wei; Wang, Chi; Shi, Hong; Zhao, Yu-Feng; Xin, Juan-Juan; Wang, Xiao-Yu; Shang, Hong-Yan; Hu, Ling; Jing, Xiang-Hong; Zhu, Bing
Abstract : The aim of this study was to explore the "intensity-response" relationship between EAS and the effect of gastric motility of rats and its underlying peripheral neural mechanism by employing ASIC3 knockout (ASIC3−/−), TRPV1 knockout (TRPV1−/−), and C57BL/6 mice. For adult male Sprague-Dawley (n = 18 ) rats, the intensities of EAS were 0.5, 1, 3, 5, 7, and 9 mA, respectively. For mice (n = 8 in each group), only 1 mA was used, by which C fiber of the mice can be activated. Gastric antrum motility was measured by intrapyloric balloon. Gastric motility was facilitated by EAS at ST36 and inhibited by EAS at CV12. The half maximal facilitation intensity of EAS at ST36 was 2.1–2.3 mA, and the half maximal inhibitory intensity of EAS at CV12 was 2.8 mA. In comparison with C57BL/6 mice, the facilitatory effect of ST36 and inhibitive effect of CV12 in ASIC3−/− mice decreased, but the difference was not statistically significant (P > 0.05 ). However, these effects in TRPV1−/− mice decreased significantly (P < 0.001 ). The results indicated that there existed an "intensity-response" relationship between EAS and the effect of gastric motility. TRPV1 receptor was involved in the regulation of gastric motility of EAS.